1999
DOI: 10.2500/105065899781389948
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Rhinometry Evaluation of Nasal Response to Histamine and Antigen in Guinea Pigs

Abstract: The effects of antigen and histamine on the changes of nasal passage patency in 112 guinea pigs with or without allergic rhinitis were evaluated by acoustic rhinometry. The percent change of volume from the nostril to 2 cm into the nasal cavity showed significant reduction of 31.10 +/- 4.11% at 10 minutes and 31.10 +/- 4.11% at 30 minutes after antigen challenge in sensitized guinea pigs. The pretreatment with ketotifen, an H1-histamine receptor antagonist as well as mast cell stabilizing drug, blocked dose-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…In addition, it has been reported that chlorpheniramine blocked early-phase nasal congestion in sensitized dogs [5]. Although chlorpheniramine and ketotifen inhibited the increase in Penh 1 h after the TDI challenge, ketotifen showed a somewhat stronger effect [3]. As for epinastine, the drug exhibited a more potent and longer lasting effect than chlorpheniramine.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, it has been reported that chlorpheniramine blocked early-phase nasal congestion in sensitized dogs [5]. Although chlorpheniramine and ketotifen inhibited the increase in Penh 1 h after the TDI challenge, ketotifen showed a somewhat stronger effect [3]. As for epinastine, the drug exhibited a more potent and longer lasting effect than chlorpheniramine.…”
Section: Discussionmentioning
confidence: 96%
“…One of the typical symptoms in allergic rhinitis is nasal congestion. Nasal congestion associated with allergic rhinitis may be due to the increased nasal blood flow causing increased filling and distention of the venous erectile tissue, which develops an edematous swelling of the nasal mucosal membrane [3]. Since nasal congestion in human beings is a subjective symptom, it is therefore difficult to evaluate in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a receptor binding assay and measurements by acoustic rhinometry, it is suggested that sensitization with allergen increases the number of histamine H1 receptors. The increased number of H1 receptors in the nasal mucosa of sensitized guinea pigs may be one of the causes of nasal hyperresponsiveness to antigen (434, 435). The vascular effects of sensory peptides have also been examined (436).…”
Section: Other Clinical Uses Of Acoustic Rhinometry and Acoustic Reflmentioning
confidence: 99%
“…The method was first used in laboratory animals (guinea pigs) in 1994 (23). Since then, a small number of studies have used AR to describe the effect of pharmacological interventions on the nasal mucosa in guinea pigs (11,12,(19)(20)(21)24).…”
mentioning
confidence: 99%